2012
DOI: 10.1016/j.jchromb.2012.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Breath biomarkers of liver cirrhosis

Abstract: The diagnosis of asymptomatic cirrhosis in patients with liver disease is of importance to start screening for complications in due time. Liver biopsy is neither sensitive nor practical enough to be used as a frequent follow-up test in patients with chronic liver disease. The volatile organic compounds present in exhaled breath offer the possibility of exploring internal physiologic and pathologic process in a non invasive way. This study examined whether a specific pattern of biomarkers can be found in breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 42 publications
6
53
1
Order By: Relevance
“…16,19 In our study, the levels of carbon disulfide and dimethyl sulfide were significantly elevated in PSC patients (irrespective of the presence or absence of cirrhosis) when compared to patients with CCA.…”
Section: Discussionsupporting
confidence: 46%
“…16,19 In our study, the levels of carbon disulfide and dimethyl sulfide were significantly elevated in PSC patients (irrespective of the presence or absence of cirrhosis) when compared to patients with CCA.…”
Section: Discussionsupporting
confidence: 46%
“…Accordingly, it has been shown that the exhaled breath of cirrhotic patients is enriched of alkanes, alkenes, terpenes, ketones and S‐compounds compared to healthy controls . An impaired liver metabolism is certainly involved, and these compounds are likely the result of oxidative stress and of altered hepatic cytochrome P450 enzyme activity . Furthermore, S‐compounds may be generated by incomplete metabolism of methionine in the transamination pathway, as well ketones could be expression either of an increased insulin resistance in cirrhotic patients—which favours lipolysis and free fatty acid beta‐oxidation—or of glycogen exhaustion and gluconeogenesis impairment in the late phases of hepatocellular failure .…”
Section: Discussionmentioning
confidence: 99%
“…Alkanes are known to be produced by oxidative stress [17] and fatty acid metabolism. Giardia has developed elaborate sequences of adaptive mechanisms to maintain oxygen homeostasis and equilibrium [18].…”
Section: Discussionmentioning
confidence: 99%